Community Participation in the Management of Suranadi Nature Tourism Park in West Lombok Regency - Widiantari, Laely; Anwar, Hairil; Ichsan, Andi Chairil (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Suranadi Nature Tourism Park, a rather well-known location in West Lombok Regency, is one of the conservation places that the NTB administration is presently working on. Up until now, the Suranadi Nature Tourism Park region has been managed primarily with the goal of maintaining the territory's worth and purpose. Therefore, it is necessary to conduct research to determine the form and level of community participation in the management of the Suranadi Nature Tourism Park starting from the planning, implementation, to evaluation stages and to understand the factors that encourage the community to participate in the management of the Suranadi Nature Tourism Park. The method used in this study is a qualitative descriptive method. Data were analyzed using multiple linear regression, then tested the hypothesis, namely with the t-statistical test (t-test) and the F-test. According to the study's findings, there are three stages to the community's involvement in the management of Suranadi Nature Tourism Park: the planning stage, wherein community ideas and opinions are incorporated; the implementation stage, wherein involvement is split into two categories: labor and skill participation and property/investment participation; and the evaluation stage. With a score of 204, the degree of community involvement in the planning, execution, and assessment phases falls into the moderate range. According to the regression model derived for the elements impacting community engagement in Suranadi Nature Tourism Park management, it is separated into two categories: internal factors. Of these, income level, location distance, and employment account for 32.1% of the factors influencing community participation.